(untitled) (Asian Journal of Medical and Biological Research, 2023)
Birds are mainly categorized as either monomorphic or dimorphic based on phenotypic characteristics. It is believed that nearly 60 % of the bird species are monomorphic and difficult to distinguish the sex during their early stages of life. It is important to identify the different sexes at a distance when birds are in the wild or in natural habitats, especially for bird lovers, biologists and conservationists to differentiate the behavioral patterns of birds. However, even aviculturists and experienced biologists have faced difficulties in identifying the different sexes of monomorphic birds at a distance. The key genes responsible for the sex differentiation of chickens are unclear due to their multiple gene expressions. Therefore, the sex determination of birds is more important in aviculture, poultry farming and in research fields. Hence, this review mainly focused on those invasive (laparoscopy), moderately invasive/ minimally invasive (Karyotyping and DNA-based techniques), and non-invasive methods (steroid sexing, vent sexing, morphometric observations, voicing) of sex identification of birds as much as possible and discussed the reliability of those techniques on the identification of the sex of birds. In light of the discussion, the accuracy of non-invasive techniques is very low and quite questionable. Despite the high accuracy, laparoscopy poses a life threat to the birds during the surgery due to the damage of internal organs while probing. DNA-based methods are concluded to be the best and most accurate techniques among almost all the techniques that require sophisticated laboratory facilities. Hence, the on-farm approach of Recombines polymerase amplification combined with a lateral-flow dipstick (RPA-LFD) can be suggested as one of the best alternatives to laboratory protocols that can be practiced without bringing down the accuracy of the sex determination of birds. Asian J. Med. Biol. Res. 2023, 9 (4), 134-144